TPC Together with Overlapped Time Domain Multiplexing System Based on Turbo Structure - Zheng, Hao; Xing, Mingjun; Yue, Yutao; Li, Xue; Li, Daoben; Ji, Chunlin (Discoveries in Agriculture and Food Sciences, 2017)
Overlapped time domain multiplexing (OvTDM) is a novel technique for utilizing inter-symbol interference (ISI) to benefit a communication system. We implement the OvTDM technique based on turbo structure and associate a turbo product code (TPC) to construct a novel coded turbo-structure OvTDM system. Two schemes of the iterative receiver and soft-input and soft-output (SISO) decoding algorithms are presented. Simulation results show an attractive advantage and performance of designed structures.